Plantifully simple : 100 plant-based recipes and meal plans for health and weight loss - Nelson, Kiki; Holtzman, Rachel (Simon Element, 2024)
"Whether you want to prevent diabetes and stroke, sleep better, heal PCOS, resolve any number of health concerns associated with weight, are trying to shed those last ten pounds, or you are simply in a maintenance stage, Plantifully Simple is for you. Kiki Nelson, who lost seventy pounds on a plant-based diet and eliminated her risk for diabetes and stroke, shares the recipes, meal plans, plate-building, and mindset she adopted to reclaim her health-and keep off the weight. Here, she offers 100 all-new recipes that are as delicious as they are satisfying: they depend on luscious fruits and vegetables as well as comforting and satisfying carbs so you will never be bored or hungry-or feel restricted. Kiki knows that to lose weight you need a plan, and here she offers two foolproof plans. Both can deliver results, and offer freedom and peace of mind when it comes to making food choices"--